Relieving treatment of bronchial asthma attack in schoolchildren suffer from severe disease phenotype - Garas, Mykola; Lekhkun, Gennadіy; Lysenko, Vladislav; Natalia, Basiuk (ScienceRise: Medical Science, 2017)
The study aimed at improving relieving treatment of bronchial asthma attacks in children of school age with a severe phenotype of the disease. Materials and methods. On the base of pulmonological department of the Regional Pediatric Hospital (Chernivtsi) 57 school-age children with severe persistent asthma were examined, the attack period was determined in 48 patients (84,2 %). The severity of bronchial obstruction syndrome on patients’ admission to the hospital during the exacerbation period was assessed by point scale. Therapeutic tactics in the period of attack was assigned according to the protocol for diagnosis and treatment of asthma in children. It was determined that in patients with severe bronchial asthma for the purpose of desobstruction short-acting inhalation β2-agonists, steroids of systemic effect and methylxanthines preparations (Euphylline) were administered for oral and intravenous use in various combinations with one another. 80,0 % of children with severe bronchial asthma received steroids of systemic effect, the average duration of the course was 2,9±0,19 days. Most children with severe bronchial asthma (52,9 %) in acute period of the disease received infusion therapy with methylxanthines (Euphylline), the average duration of infusion therapy in children with severe pathology persistence lasted 3,3±0,24 days. Systemic use of glucocorticosteroids and infusion therapy with methylxanthines (Euphylline) possess distinct clinical effect, since it was considered appropriate to analyze the frequency of their administration during the first three days of hospital treatment. Result. Relieving treatment with steroids of systemic effect during 3 days the attack severity regress was observed on the seventh day of hospitalization compared to the first day, so reduce relative risk of preserving severe bronchial obstruction reached 80 %, the reduce attributive risk was 67 % with the number of patients to be treated – 1,5 children. Intravenous Euphylline administration in children with severe variant of the disease causing regression of bronchial obstruction, the reduce relative risk of severe bronchial obstruction on the seventh day of hospitalization in patients with severe bronchial asthma reached 74 %, reduce attributive risk was 63 % with the number of patients to be treated – 1,5 children. Conclusions. Thus, these data give reason to prove the value of initial three-day course administration of steroids of systemic effect and intravenous Euphylline administration in the treatment of attack period in children with severe bronchial asthma